2017
DOI: 10.1007/s11356-017-9410-x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and regeneration of feather keratin in NMMO solution

Abstract: Chicken feather, a potential source of keratin, is often disposed as waste material. Although some methods, i.e., hydrolysis, reduction, and oxidation, have been developed to isolate keratin for composites, it has been limited due to the rising environmental concerns. In this work, a green solvent N-methylmorpholine N-oxide (NMMO) was used to extract keratin from chicken feather waste. Eighty-nine percent of keratin was extracted using 75% NMMO solution. However, the result from size exclusion HPLC showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…29 However, in this study, the GA addition did not improve the strength properties, which may indicate that new cross-links neither formed nor were they enough to improve the tensile strength. It is suggested that GA reacts with the amino groups of lysine, 28,33 and the content of lysine in feather keratin is low, 9 which could explain the low degree of cross-linking.…”
Section: Deep Eutectic Solvent Fractionation and Lm Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, in this study, the GA addition did not improve the strength properties, which may indicate that new cross-links neither formed nor were they enough to improve the tensile strength. It is suggested that GA reacts with the amino groups of lysine, 28,33 and the content of lysine in feather keratin is low, 9 which could explain the low degree of cross-linking.…”
Section: Deep Eutectic Solvent Fractionation and Lm Preparationmentioning
confidence: 99%
“… 8 The chemicals used for these reactions are often toxic, poorly recyclable, and expensive to produce. Green solvents, N -methylmorpholine N -oxide (NMMO) 9 and ionic liquids (ILs), 10 have been used to dissolve feathers. The green solvents are considered to possess similar physiochemical characteristics with each other such as low volatility, non-flammability, low melting point, low vapour pressure, dipolar nature, chemical, and thermal stability, high solubility, and tuneability.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 ILs have also demonstrated their capacity in keratin extraction from wool 10,11 and feathers. [12][13][14][15][16][17] Deep eutectic solvents (DESs) are a rather new type of solvents used in biomass processing. They were rst presented by Abbott et al 18 as alternative solvents for ILs.…”
Section: Introductionmentioning
confidence: 99%
“…40 Besides the decrease in molecular weight, a part of this ordered structure and cysteine residues of keratin were lost during the processing. 10,12,13 This could indicate that the keratin used in this study transformed from a highly ordered protein to more labile, unstructured peptides.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“… 11 Similar observations of keratin molecular weight distributions have also been reported after N -methylmorpholine N -oxide (NMMO) treatment for feathers. 13 Although the low Mw fraction was initially water soluble in the presence of diluted DES components, the low-Mw keratin fraction was not completely soluble in pure water or in the used buffers after dialyzing and freeze-drying. This indicated that further structural modification might have occurred during the drying process or the absence of the diluted DES components decreased the solubility.…”
Section: Resultsmentioning
confidence: 99%